2008
DOI: 10.1038/jcbfm.2008.81
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment with Rosuvastatin Protects Insulin Resistant (C57BL/6J ob/ob) Mice against Transient Cerebral Ischemia

Abstract: The purpose of this study was to investigate the short-term effects of rosuvastatin (RSV), a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, on transient, focal cerebral ischemia in C57BL/6J ob/ob mice with insulin resistance (IR). Male ob/ob, lean, or wild-type (WT) mice were treated with RSV (10 mg/kg per day, i.p.) or vehicle for 3 days. Ischemia was induced by 60 mins of middle cerebral artery occlusion (MCAO) and cortical blood flow (CBF) was monitored by laserDoppler flowmetry. Infarct volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…We and others have characterized many of the general cardiovascular effects of this disease (19,(51)(52)(53)85,87,94,112,119) and have shown that tissue and vascular inflammation and increased basal levels of ROS from both mitochondrial and nonmitochondrial sources are responsible for vascular and cardiac dysfunction (19,119).…”
Section: Vascular Mitochondria In Insulin Resistancementioning
confidence: 99%
“…We and others have characterized many of the general cardiovascular effects of this disease (19,(51)(52)(53)85,87,94,112,119) and have shown that tissue and vascular inflammation and increased basal levels of ROS from both mitochondrial and nonmitochondrial sources are responsible for vascular and cardiac dysfunction (19,119).…”
Section: Vascular Mitochondria In Insulin Resistancementioning
confidence: 99%
“…However, our own experience suggests that despite marginally extended surgery times, subcutaneous adiposity does not unduly affect success rates. This is also borne out by the recent studies that have emerged combining experimental obesity and stroke (119)(120)(121)(122). All such studies have found that the severity of brain damage is markedly increased in obese rodents compared to corresponding wild-types (see below).…”
Section: Zucker (Fa/fa) Ratsmentioning
confidence: 88%
“…It is only in the last 2 years that studies investigating the impact of obesity on experimental stroke in rodents have emerged (119)(120)(121)(122). All studies have found significantly increased ischemic brain damage in the obese group (see Table).…”
Section: Zucker (Fa/fa) Ratsmentioning
confidence: 99%
“…Mice were anesthetized with pentobarbital sodium (0.06 g/kg) by intraperitoneal injection. Focal ischemia was induced with minor modifications of Tamura's middle cerebral artery occlusion (MCAO) model (Mayanagi et al, 2008). Briefly, the left common and external carotid arteries were exposed through a ventral midline neck incision and were ligated, respectively.…”
Section: Methodsmentioning
confidence: 99%